2017
DOI: 10.1016/j.clcc.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neutrophil to Lymphocyte Ratio Improves Prognostication in Colon Cancer

Abstract: Background We studied the role of peripheral Neutrophil to Lymphocyte Ratio (NLR) on survival outcomes in colon and rectal cancer to determine if its inclusion improved prognostication within existing staging systems. Patients and Methods Disease free and overall survival (DFS and OS) Hazard Ratios (HR) of pretreatment NLR were calculated for 2536 stage I-III colon or rectal cancer patients and adjusted for age, positive/total number of nodes, T stage, and grade. The association of NLR with clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
(30 reference statements)
5
29
0
Order By: Relevance
“…The 2-year OS and DFS of stage III CC are reported as 65.9% and 59.2%, respectively, in the literature. 20 The figures of the resectable tumors are 94.1% and 77.5%. 21 Our results of follow-up indicated that NACRT made the survivals of the patients with unresectable disease improve towards those of the patients with resectable disease.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-year OS and DFS of stage III CC are reported as 65.9% and 59.2%, respectively, in the literature. 20 The figures of the resectable tumors are 94.1% and 77.5%. 21 Our results of follow-up indicated that NACRT made the survivals of the patients with unresectable disease improve towards those of the patients with resectable disease.…”
Section: Discussionmentioning
confidence: 99%
“…The association between colon cancer and lymphocyte counts has been examined in studies as early as the 1970s, in which a decrease in lymphocyte counts was found in patients with more advanced colon cancer [ 21 ]. Additionally, as one of the potential predictive markers, an elevated preoperative NLR was found to be a predictor of recurrence and worse survival after resection of CRC [ 17 , 22 , 23 ]. In the present study, RFS and OS of stage II colon cancer were found to be highly correlated with decreased lymphocyte counts, though preoperative NLR was not found to be an independent prognostic variable for recurrence of stage II colon cancer, as previously reported [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Walsh et al rst reported a correlation between preoperatively elevated NLR had a relationship with overall and cancer-speci c survival in colon cancer [24]. The predictive potential of NLR in evaluating the prognosis of patients with various types of malignancies, including resectable colon cancer, has been demonstrated in previous studies [8][9][10][11]. However, no study has analyzed a large cohort of patients with Stage II-III advanced colon cancer using propensity scores to minimize selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, neutrophil-to-lymphocyte ratio (NLR) is calculated from white blood cell (WBC) differential counts and can be obtained easily in preoperative patients. Previous studies have reported on the predictive potential of NLR as a prognostic factor in various types of malignancies, including resectable colon cancer [8][9][10][11][12][13][14]. However, since these previous studies analyzed data by univariate or multivariate analysis, the possibility of selection bias and confounding factors could not be ruled out.…”
Section: Introductionmentioning
confidence: 99%